Ascorbate−glutathione cycle involving in response of Bangia fuscopurpurea (Bangiales, Rhodophyta) to hyposalinity - Niu, Citong; Wang, Wenjun; Yao, Haiqin; Liang, Zhourui; Zhang, Pengyan; Lu, Xiaoping (Frontiers in Marine Science, 2023)
Bangia fuscopurpurea is a widespread intertidal seaweed that is commercially cultured in China. This seaweed is frequently exposed to hyposalinity stress, but little is known about the adaptation mechanisms. Ascorbate−glutathione (AsA−GSH) cycle plays important roles in many organisms under a variety of abiotic stress, including hyposaline stress. In this study, we investigated the response of key metabolites and enzymes involved in the AsA−GSH cycle of B. fuscopurpurea under hyposalinity, with the addition of exogenous GSH and Lbuthionine-sulfoximine (BSO). The quantification of BfAPX gene expression was assessed across varied treatment regimens. And the putative interaction proteins of BfAPX were screened by yeast two hybrid system. It was found that under hyposalinity (15 and/or 0 psu), the content of reduced glutathione (GSH), total glutathione (GSH+ oxidized glutathione, GSSG) and cysteine, the ratio of GSH/GSSG and ascorbic acid (AsA)/ dehydroascorbic acid (DHA), and the activity of ascorbic acid peroxidase (APX) and monodehydroascorbate reductase (MDHAR) was significantly up-regulated. The hyposality-promoted GSH/GSSG was weakened while the glutathione reductase (GR) activity was promoted by adding exogenous GSH and BSO. The hyposality-promoted AsA/DHA ratio was strengthened by exogenous GSH but weakened by BSO. The dehydroascorbate reductase (DHAR) activity had no significant changes either with or without exogenous GSH under all salinities, while DHAR activity together with DHA content was enhanced by BSO. The expression of APX gene markedly increased under hyposalinity+BSO treatment. Putative interacting proteins of APX, including glutamate dehydrogenase 1a and fructose diphosphate aldolase, were identified through screening. The results indicated that the AsA−GSH cycle was involved in response of B. fuscopurpurea to hyposalinity by means of increasing GSH/GSSG ratio (through promoting GSH biosynthesis pathway and GSH regeneration from GSSG by GR catalyzation) and AsA/DHA ratio (promoting AsA regeneration through MDHAR). These findings would contribute to improve the aquaculture of this promising economic species and unveil how intertidal seaweeds address the global climate challenges.